The molluscum contagiosum BOTE sign—Infected or inflamed?. Issue 3 (1st March 2020) - Gross, Itai; Ben Nachum, Noa; Molho‐Pessach, Vered; Weiser, Giora; Oster, Yonatan; Engelhard, Dan; Megged, Orli; Hashavya, Saar
Abstract: Background: Molluscum contagiosum (MC) is a common skin infection in the pediatric age group. The infection is self‐limited and manifests as discrete, umbilicated skin‐colored papules on any skin surface of the body. At times, complications such as local dermatitis and swelling, erythema, and pus formation may appear. These signs of inflammation are commonly presumed to represent bacterial infection. Methods: This multicenter study was a retrospective analysis of data collected on all patients diagnosed with inflamed lesions secondary to MC and treated at the Hadassah Medical Centers and Shaare Zedek Medical Center in Jerusalem, Israel, from 1/1/2008 to 1/07/2018. Characteristics of children with positive cultures were compared to those with negative cultures and those with contaminants. Results: A total of 56 cases were reviewed; the mean age at presentation was 4.6 years. Fever was reported in 12.5%, and 62.5% received systemic antibiotics because of their inflamed MC prior to admission. Fifty‐five percent had sterile cultures or cultures growing only contaminants. Only seven had positive cultures with the common cutaneous pathogens . No statistical difference was observed between the patients with pathogenic isolates and patients with sterile or non‐pathogenic cultures in terms of demographics, lesion characteristics, inflammatory markers, or length of hospitalization. Conclusion: The findings suggest that most cases of suspected MC‐related secondary infection can be attributed to inflammation rather than to bacterial infection. However, in some cases, true bacterial infection should be suspected and treated accordingly.